Human dental pulp stem cells modulate pro-inflammatory macrophages both through cell-to-cell contact and paracrine signaling - Maccaferri, Monia; Pisciotta, Alessandra; Carnevale, Gianluca; Salvarani, Carlo; Pignatti, Elisa (Frontiers in Immunology, 2024)
Introduction Macrophages play a key role in most of the inflammatory diseases such as Rheumatoid Arthritis (RA), but the mechanism underlying their pathogenesis is still under study. Among stem cells, human dental pulp stem cells (hDPSCs) have attracted attention due to their easy accessibility and immunomodulatory properties, making them a promising adjuvant therapy. In this study, we aimed to evaluate the capacity of hDPSCs to modulate the phenotypes of primary human macrophages. Additionally, we sought to observe the differences induced on macrophages when cultured directly with hDPSCs or through a cell culture insert, mimicking the paracrine communication pathway. Methods Monocytes, isolated from buffy coats, were differentiated into pro-inflammatory M1 and anti-inflammatory M2 macrophages. Subsequently, they were cultured with hDPSCs either directly or via a cell-culture insert for 48 hours. Finally, they were analyzed for protein, gene expression, cytokines levels and immunofluorescence. Results In our study, we have demonstrated that, hDPSCs, even without priming, can reduce TNFα levels and enhancing IL-10 release in pro-inflammatory macrophages, both through direct contact and paracrine signaling. Furthermore, we found that their effects are more pronounced when in cell-to-cell contact through the decrease of NF-kB and COX-2 expression and of CD80/PD-L1 colocalization. HDPSCs, when in contact with macrophages, showed enhanced expression of NF-kB, COX-2, ICAM-1, PD-L1, FAS-L, TNFα and IFNγ. Conclusion We showed that hDPSCs exert immunomodulatory effects on pro-inflammatory macrophages, with cell-to-cell contact yielding a more pronounced outcome compared to paracrine signaling. Our work highlights the immunomodulatory properties of hDPSCs on activated pro-inflammatory macrophages and the potential therapeutic role in inflamed tissue.